DAMPAK BEBAN KERJA DAN KOMPENSASI TERHADAP LOYALITAS KARYAWAN CV. X - Alfiah Lia Rahmawati; Sulastri Irbayuni (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
Optimal human resource management is crucial, as high-quality human resources determine both organizational success and employee loyalty. However, companies today face significant challenges regarding suboptimal loyalty, coupled with weaknesses in compensation structures and high workloads, which can hinder performance and organizational stability. This study aims to determine and analyze the influence of workload and compensation on employee loyalty at CV. X. The population of this study consists of all 53 employees. The sampling technique used is non-probability sampling with a purposive sampling method, resulting in 40 respondents. These respondents consist of production department employees at CV. Duta Jaya Makmur who meet the criteria of being active employees currently working in and directly involved with the production process. This research adopts a quantitative approach. Data collection was conducted by distributing questionnaires via Google Forms. Data analysis was performed using Partial Least Square (PLS). The results of the study indicate that workload and compensation contribute significantly to employee loyalty.